Khuld-i barīn : Rawḍahā-yi shīshum u haftum-Tārīkh-i Tīmūriyān u Turkmānān - Qazwīnī, Muḥammad Yūsuf Wālih, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Islamic world, universal histories have been written almost from the very beginning. Among the Arabic works one could, for example, mention the Kitāb akhbār al-rusul wal-mulūk by Abū Jaʿfar al-Ṭabarī (3rd/9th cent.), Ibn Miskawayh's (d. 421/1030) Kitāb tajārib al-umam , or the Mukhtaṣar taʾrīkh al-bashar by Abu ʼl-Fidāʾ (d. 732/1331). The first such history in New Persian was the abstract of Ṭabarī's Akhbār that was made by Abū ʿAlī Balʿamī (d. between 382-87/992-97) for the Samanid emir Manṣūr b. Nūḥ (d. 365/976). Many other works followed, such as Rashīd al-Dīn Hamadānī's Jāmiʿ al-tawārīkh (composed in 699-710/1300-10) or the Tārīkh-i Ḥāfiẓ Abrū by Ḥāfiẓ Abrū (d. 833/1430). The present work by Muḥammad Yūsuf Wālih Qazwīnī (d. after 1078/1667) is a universal history with a focus on the Safavids. The sections published here describe the history of the Timurids and the Aq and Qara Qoyunlu dynasties, vital to our understanding of the rise of the Safavids.